Evaluasi Tata Kelola Teknologi Informasi menggunakan Framework COBIT 4.1 Domain Plan and Organise (PO) dan Acquire and Implement (AI) Studi pada Dinas Komunikasi dan Informatika Kabupaten Sidoarjo - Tri Wahyu Riski; Suprapto Suprapto; Yusi Tyroni Mursityo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The Department of Communication and Information of Sidoarjo is a government agency whose task is to carry out authority in the field of communication and informatics. The field that handles IT governance namely the field of information development. Based on interviews, observation and questionnaires there were several problems, like not optimal system maintenance in applications that are in the process of development, and the lack of SDM in IT knowledge so that when IT infrastructure maintenance involves a third part, and the lack of optimal IT resource procurement is indicated by the selection qualifications of partners who are not yet on target. Based on results obtained, the average value of the maturity level for Plan and Organize domain (PO) is 2.3 (repeatable level) and Acquire and Implement (AI) is worth 2.28 (repeatable level). Diskominfo Sidoarjo needs to make efforts to increase the maturity so that the current maturity level value is obtained as expected. Some recommendations were generated such as, increasing human resources which still lack knowledge in the IT field, endorsing and disseminating guidelines for software maintenance with district district authorities at Diskominfo Sidoarjo.